Transverse Aeolian Ridge Growth Mechanisms and Pattern Evolution in Scandia Cavi, Mars - Fenton, Lori K.; Silvestro, Simone; Kocurek, Gary (Frontiers in Earth Science, 2021)
In Scandia Cavi on Mars, barchans migrating over a field of transverse aeolian ridges (TARs) leave behind distinctive trails (“wakes”) comprising both TARs undergoing exhumation and coarse-grained ripples being shed from the barchans. With distance upwind from the barchans, the combined pattern of these bedforms coarsens and defect density decreases, thus appearing to mature with exposure time. We present results of morphological analyses of the wake bedform crestlines using HiRISE images, seeking to determine how the wake pattern reflects TAR growth and pattern development. TARs interact with each other, exhibiting defect repulsions and possible lobe extensions, indicating that these bedforms have migrated in the past, despite the lack of identifiable change in overlapping images spanning 9.5 years. Mapping one wake in detail, we found that the TAR pattern is not affected by superposing ripples. However, the ripples undergo many interactions, first with one another, and later (with distance upwind) with the underlying TARs. Near the dune, many ripples laterally link, growing in length, and they preferentially form along TAR crests, resulting in small bedform repulsions and longer superposing ripples. Most of these ripples will be consumed by the TARs, an as-yet unreported growth dynamic for TARs that is consistent with the work of others, who have found a continuum between TARs and the meter-scale ripples that form on dunes. Constructing a DTM, orthorectifying HiRISE images, and measuring dune migration rates places the timescale of ripple absorption by TARs in a wake at several thousand years, with the first ∼1,000 years dominated by lateral linking of ripples. Assuming that TAR growth is accomplished entirely through dune burial and subsequent ripple consumption, we estimate a lower limit age of the TARs, and by extension, the dune field, to be ∼270 kyr.